A Note on the High Stability of Happiness: The Minimal Effects of a Nuclear Catastrophe on Life Satisfaction - Eva M. Berger (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Using life satisfaction as a direct measure of individual utility has become popular in the empirical economic literature. In this context, it is crucial to know what circumstances or changes the measure is sensitive to. Is life satisfaction a volatile concept that is affected by minor changes in life circumstances? Or is it a reliable measure of personal happiness? This paper will analyze the impact of a catastrophe, namely the nuclear catastrophe of Chernobyl, on life satisfaction. I use longitudinal data from the German Socio-Economic Panel Study and especially information collected on a monthly basis which allows the researcher to study calendar effects. The following clear-cut results are found. While concern about the environment rose immediately after the nuclear incident, life satisfaction changed little. This suggests that although people were aware of the severity of the catastrophe, they did not feel that their individual well-being had been affected. This finding is highly relevant to the life satisfaction literature as it shows that the life satisfaction measure is very stable and robust against societal and global events. It is shown to predominantly reflect personal life circumstances like health, employment, income, and the family situation and this relationship is apparently not disturbed by global events. Thus, my results reinforce previous findings on the relationship between life satisfaction and individual life characteristics as the stability of their outcome measure is approved.
Keywords: I31; A12; A19; 330; Subjective Well-Being; Happiness; Environmental Protection; Household Panel; SOEP